Average Treatment Effect Bounds with an Instrumental Variable: Theory and Practice - Flores, Carlos A. (Springer Singapore, 2018)
This book reviews recent approaches for partial identification of average treatment effects with instrumental variables in the program evaluation literature, including Manski's bounds, bounds based on threshold crossing models, and bounds based on the Local Average Treatment Effect (LATE) framework. It compares these bounds across different sets of assumptions, surveys relevant methods to assess the validity of these assumptions, and discusses estimation and inference methods for the bounds. The book also reviews some empirical applications employing bounds in the program evaluation literature. It aims to bridge the gap between the econometric theory on which the different bounds are based and their empirical application to program evaluation.